Original Research: Feasibility and safety of two surgical techniques for the development of an animal model of jugular vein occlusion. Issue 1 (January 2017) - Auletta, Luigi; Greco, Adelaide; Albanese, Sandra; Meomartino, Leonardo; Salvatore, Marco; Mancini, Marcello
To date, no studies have explored the effect of abnormal cerebral venous circulation on brain disorders, whereas many studies have investigated neurodegenerative brain anomalies associated with arterial diseases. The aim of our study was to demonstrate the feasibility of different surgical techniques to induce venous obstruction of cerebral brain drainage. Six C57/black mice underwent bilateral occlusion of the external jugular vein (group EJV ), six underwent bilateral occlusion of the internal jugular vein (group IJV ), and six underwent bilateral occlusion of both the EJV and the IJV (group EJV/IJV ). Within each group, the interruption of blood flow was obtained via monopolar electro-coagulation (ME) in three mice and via surgical ligation (SL) in the remaining three mice. A "sham group" of two mice was used as the control. High-frequency ultrasound (HFUS) was used to detect the absence of blood flow in the examined vessel. The ME procedure led to successful results in two of nine (22%) mice, one in the EJV group, one in the EJV/IJV group, and zero in the IJV group, and 4 of 18 (22%) mice when considering individual veins (i.e., total number of EJVs and IJVs occluded). The SL procedure was successful in two of three (67%) mice in the EJV group, in three of three (100%) mice in the IJV and in three of four (75%) mice in the EJV / IJV group. Therefore, the overall success rate was 8/10 (80%) when considering mice, and 20/26 (77%) when considering individual veins. The monopolar electro-coagulation method exhibited a high mortality due to cardiorespiratory arrest, while the results of the bilateral surgical ligation of EJVs and IJVs show that it is technically feasible and safe.